Dari Dakwah Verbal Menuju Dakwah Pemberdayaan: Relevansi Gerakan Jama’ah dan Dakwah Jama’ah Muhammadiyah dalam Konteks Masyarakat Modern - Solihin, Mohammad; Jamroji, Bagus; Ardila, Yopi; Yakin, Ahmad (Educational Research Center, 2026)
Social changes driven by modernization, urbanization, and the rapid growth of digital communication have reshaped the landscape of Muslim religiosity in Indonesia and generated new challenges for da’wah practices. Da’wah that predominantly relies on verbal and ceremonial modes is often considered insufficient to address structural problems faced by communities, including socio-economic inequality, limited access to education, family economic vulnerability, and value disorientation in digital spaces. This article aims to analyze the paradigm shift from verbal da’wah to empowerment-oriented da’wah through Muhammadiyah’s Gerakan Jama’ah dan Dakwah Jama’ah (GJDJ) and to examine its relevance in modern society. Employing a qualitative literature review, this study draws on scholarly journals, academic books, and relevant institutional documents published mainly within the last decade. The findings indicate that GJDJ constitutes a transformative da’wah model that integrates spiritual, social, and structural dimensions by positioning the jama’ah as the core of da’wah activities. GJDJ is particularly relevant for strengthening social cohesion, encouraging collective participation, and developing contextual and sustainable empowerment programs. These findings suggest that GJDJ functions not only as an internal organizational strategy but also as an adaptable da’wah framework for responding to contemporary social change in the digital era.